Will iPSC-cardiomyocytes revolutionize the discovery of drugs for heart disease?. (October 2018) - Bruyneel, Arne AN; McKeithan, Wesley L; Feyen, Dries AM; Mercola, Mark
Highlights: Physiological screening of iPSC-CMs is a powerful new tool for drug discovery. Advantages include human genetics, cellular context and throughput. Caveats include immature metabolic, mechanical and electrical physiology. The platform might revolutionize some, but clearly not all, applications. Abstract : Cardiovascular disease remains the largest single cause of mortality in the Western world, despite significant advances in clinical management over the years. Unfortunately, the development of new cardiovascular medicines is stagnating and can in part be attributed to the difficulty of screening for novel therapeutic strategies due to a lack of suitable models. The advent of human induced pluripotent stem cells and the ability to make limitless numbers of cardiomyocytes could revolutionize heart disease modeling and drug discovery. This review summarizes the state of the art in the field, describes the strengths and weaknesses of the technology, and applications where the model system would be most appropriate.